Mercy Hill : a novel - Thurman, Hannah (Doubleday, 2026)
"A debut family novel about four sisters growing up on the campus of the underfunded state mental hospital where their strong-willed mother serves as head of psychiatry. A richly moving story of sisterhood, loyalty, and mental health in America. The Cross sisters have lived their entire lives on the sprawling grounds of Mercy Hill, the embattled Raleigh mental hospital run by their formidable mother. Since childhood, JJ, Caro, Mimi, and Denise have been inculcated with their mother's mission: they'll work alongside her to protect Mercy Hill from the fate of other state hospitals across the country, which are being gutted and closed, one by one. After an incident involving the highest security ward, Mercy Hill faces greater scrutiny than ever, and Lisa Cross pushes each of her daughters even harder in the name of her mission. As the sisters cross into adulthood, the pressures of their isolated environment and mercurial mother set them on different - and perilous - paths. And as the battle wages on, youngest sister and narrator Denise grapples with the added responsibility that comes from being the last hope for their mother's dreams. Set in the late 1990s and early 2000s, with Mercy Hill's fate hanging in the balance, Denise recounts the transformations that shape and destroy her family, along with the landscape of mental healthcare in the United States. With sharp insight and real humor, debut novelist Hannah Thurman captures the turmoil of growing up, the true meaning of a calling, and the indelible bonds of family"-- Provided by publisher.